2020
DOI: 10.3390/jcm9061867
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacovigilance Study of Hydroxychloroquine Cardiac Safety Profile: Potential Implication in COVID-19 Mitigation

Abstract: In light of the favorable outcomes of few small, non-randomized clinical studies, the Food and Drug Administration (FDA) has issued an Emergency Use Authorization (EUA) to Hydroxychloroquine (HCQ) for hospitalized coronavirus disease 2019 (COVID-19) patients. In fact, subsequent clinical studies with COVID-19 and HCQ have reported limited efficacy and poor clinical benefits. Unfortunately, a robust clinical trial for its effectiveness is not feasible at this emergency. Additionally, HCQ was suspected of causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Another fundamental fact that must be considered is that the FDA issued a statement against hydroxychloroquine and chloroquine for COVID-19 use outside the hospital setting due to safety concerns, especially related to heart problems. This did not include FDA-approved uses for malaria and autoimmune diseases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another fundamental fact that must be considered is that the FDA issued a statement against hydroxychloroquine and chloroquine for COVID-19 use outside the hospital setting due to safety concerns, especially related to heart problems. This did not include FDA-approved uses for malaria and autoimmune diseases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of acute myocardial injury and acute myocarditis in patients with COVID-19 infection, various and serious ventricular arrhythmias (VAs) may occur [15] . Other important triggers include the severe respiratory insufficiency and the systemic inflammation incurred by COVID-19 infection, as well as the proarrhythmic effects of COVID therapies and other drug interactions and also the autonomic imbalance superimposed in patients afflicted by the disease [ 5 , 9 ]. Furthermore, hypoxemia which is common in these patients and electrolyte disturbances occurring for various reasons in this group of patients may aggravate arrhythmogenicity.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…A recent disproportionality analysis of HCQ-associated CV adverse reactions using the FDA adverse event reporting system (FAERS) database of >11,901,836 datasets and 10,668,655 patient records indicated that HCQ was associated with higher reporting odds ratios (ROR) of TdP (ROR: 3.05; 95% CI: 2.30 to 4.10), complete atrioventricular (AV) block (ROR: 2.30; 95% CI: 1.55 to 3.41) and QT prolongation (ROR: 2.09; 95% CI: 1.74 to 2.52) [9] . QT prolongation and TdP are more frequent with high doses for a comparatively short period and represent the most common HCQ-associated side-effects…”
Section: Chloroquine / Hydroxychloroquinementioning
confidence: 99%
See 1 more Smart Citation
“…11 Significant cardiac adverse effects associated with HCQ such as QT-prolongation, ventricular arrhythmias, torsade de pointes (TdP), and cardiomyopathy are the prime concerns that require risk-benefit judgment in COVID-19 management. [12][13][14] Apart from cardiac side effects, it has also the potential to cause bone marrow failure, hemolysis in glucose-6-phosphate dehydrogenase deficiency cases, retinopathy, gastrointestinal disorders, hepatobiliary disorders, metabolic disorders like hypoglycemia, skeletal muscle myopathy, neuromyopathy, psychiatric disorders, and exfoliative dermatitis. 15 There are variable reports from laboratory to human use in RCTs regarding the effects of such 4-aminoquinolines in some viruses like the influenza virus, Zika virus, ebola virus, dengue virus, and chikungunya virus.…”
Section: Hydroxychloroquine -At a Glancementioning
confidence: 99%